Elucidating the mechanisms underlying the action of kenaf seed peptides mixture against gram-positive and gram-negative bacteria and its efficacy in whole milk preservation - Arulrajah, Brisha; Qoms, Mohammed S.; Muhialdin, Belal J.; Meor Hussin, Anis Shobirin; Hasan, Hanan; Zarei, Mohammad; Chau, De-Ming; Ramasamy, Rajesh; Saari, Nazamid (Elsevier, 2023)
The present study determined the in-situ antibacterial effect of cationic kenaf seed peptides mixture (KSPM) in whole milk and further comprehensively elucidated the mechanisms underlying the bactericidal action against gram-positive and gram-negative bacteria. The application experiments in artificially contaminated milk showed that KSPM at 0.5 and 1 mg/mL displayed a stable and strong bactericidal activity within 1“6 h of treatment and lasted up to two weeks storage at room and refrigeration conditions. The in-vitro mechanistic study showed that the KSPM underwent conformational changes from random coil to ±-helix and ²-sheet in the membrane-mimetic environment. The KSPM exerted its inhibitory effect in a concentration and time dependent manner through cell membrane permeabilisation associated with membrane-disrupting effects, which is characterised by the cellular material leakage. The in-silico study revealed that the peptides efficiently interacted with bacterial peptidoglycan via hydrogen bonding, electrostatic interactions and hydrophobic forces. The peptide RALPSEHNK interacted with gram-positive and gram-negative bacterial phospholipid phosphate head group mainly through electrostatic interaction. The current work indicated that KSPM exerts its bactericidal effect by membrane-targeted mechanism and it would be a promising natural candidate to control bacterial contamination in milk and dairy-based products.